Weathering and soils / produced by Intelecom. - Sadd, James; Gilfillan, David (Earth revealed, 1992)
Explains that the Cleopatra's Needle obelisk in New York City's Central Park is severely weathered after only 75 years, whereas the dry climate of Egypt has preserved similar structures in that country for millennia. Shows how weather, climate, chemicals, temperature, and type of substrate, factor into rock and soil erosion. Environmental connections are also considered.